2000
DOI: 10.1063/1.1289229
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of fluxons in narrow window junctions

Abstract: We numerically investigate the dynamics of a long window junction under the influence of a constant current bias, and intermediate damping in the junction area. The current voltage characteristics are calculated for various sizes of the passive region extension w′ and different thickness of the isolating layer in the idle region. The existence of the idle region influences the fluxon solutions, and consequently the I–V characteristics, causing the fluxons to increase their critical velocity above the Swihart v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…In the ideal case of an infinitely long junction, the electrodynamic problem posed by (a)-(c) type junctions have been solved. In particular, theoretical models for the geometrical nonlocality have analyzed the following cases: 1) edge-type junctions between thick films w λ L , neglecting internal nonlocal effects 21,29 ; 2) edge-type junctions between thin films w < λ L (Pearl's limit) 18,28,30 ; 3) edge-type and 4) ramp type junctions between films of arbitrary width, taking into account both the internal and external nonlocal problems 24,25 ; 5) a variable thickness bridge above a ground plane 16,17 and 6) window junctions 20,26,27 . In this paper, we study the effect of geometrical nonlocality by analyzing experiments on extremely narrow long Josephson junctions, down to a width w of 0.1 µm.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the ideal case of an infinitely long junction, the electrodynamic problem posed by (a)-(c) type junctions have been solved. In particular, theoretical models for the geometrical nonlocality have analyzed the following cases: 1) edge-type junctions between thick films w λ L , neglecting internal nonlocal effects 21,29 ; 2) edge-type junctions between thin films w < λ L (Pearl's limit) 18,28,30 ; 3) edge-type and 4) ramp type junctions between films of arbitrary width, taking into account both the internal and external nonlocal problems 24,25 ; 5) a variable thickness bridge above a ground plane 16,17 and 6) window junctions 20,26,27 . In this paper, we study the effect of geometrical nonlocality by analyzing experiments on extremely narrow long Josephson junctions, down to a width w of 0.1 µm.…”
Section: Introductionmentioning
confidence: 99%
“…Nonlocal models can be divided into two groups, those treating internal nonlocality inside bulk junctions 14,15 , and those dealing with nonlocal effects due to outer stray fields resulting from the geometry of the junction and its electrodes 16,17,18,19,20,21,22,23,24,25,26,27,28,29 . The latter group of theories takes into account the field configuration not only inside the junction, but also around it, and incorporates the finite size of the sample and its shape-dependent magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ustinov et al [8] also display IV curves which depend on w ′ and large substructures. Recent numerical work [7] on a Josephson window junction with a lateral passive region and periodic boundary conditions along the propagation direction confirm these resonances due to Cerenkov radiation between a soliton travelling faster than v = 1 and the radiation of phase speed v φ = 1 + 1/k 2 > 1. Here we show that when the passive region exists only in the propagation direction, resonances disappear at large resolutions.…”
Section: B Discreteness Effectsmentioning
confidence: 89%
“…Using these ideas, Lee et al derived the dispersion relation for linear superconducting strip-lines [5,6]. The motion of kinks in such a window junction was studied by one of the authors using periodic boundary con-ditions in x [7]. It was shown that the speed of the kink depends on the extension of the passive region and that Cerenkov resonances occur between the cavity modes and the kink.…”
Section: Introductionmentioning
confidence: 99%